Pengaruh Pemberian Parasetamol Intravena untuk Mengurangi Nyeri Persalinan Kala 1 Fase Aktif - Sitorus, Juli; Emilia, Ova; Nurdiati, Detty Siti (JURNAL KESEHATAN REPRODUKSI, 2020)
Background: Labor was a physiological process, labor pain appeared from regularly uterine contraction, cervix distention and pressure to pelvic floor that stimulate free end nerves. Pain labor can influenced the mother, fetus and the progress of labor. There are various of effort to decrease pain labor by pharmacological or non pharmacological. The best therapy must be safe, effective, and minimal adverse effect to mother and fetus.Objective: To evaluate the effect of paracetamol intraveneous for pain relief in active labor versus saline water.Methods: In randomized controlled trial, with single blinded, 66 primigravid in active labor at RSUD Hj. ANNA LASMANAH Banjarnegara and RSUD Banyumas from November 2016 to January 2017. Sampels divided in two groups, paracetamol group (n=33) and normal saline group (n=33). The primaryÂ  outcome was the efficacy of paracetamol to relief pain. Intensity of the pain measure by VAS (visual analogue scale), pain measured before drug administration, after 30 minutes, at 1, 2, 3, and 4 hours in both groups. The secondary outcomes include the adverse effect to the mother and baby in both group.Results: The reduction in pain score was significantly greater in paracetamol group than normal saline after 30 minutes, 1, 2, 3, and 4 hours after adiministration of the drug (p<0.05). There was no adverse effect to mother and baby in both groups.Conclusion: Paracetamol intravenous statistically significant decreasing mean pain score than normal saline and safe in active labor.Keywords: Paracetamol, analgesia, active phase in labor